Design of Healthy Youth Edition Teens Based Game - Enggar Dwi Utami; Hendra Prasetya; Erdhi Widyarto Nugroho (Soegijapranata Catholic University, 2020)
In Indonesia, there are many promiscuity cases such as brawl, drug dealers and free sex among students. Therefore, the importance of having the social skills to dare to take a firm stance, to reject the negative offer of the environment needs to be owned by a teenager. In addition to the importance of self-awareness, to keep teenagers in Indonesia is not easy to fall into a healthy association it is also necessary to help socialize and provide education about healthy association for today's teenagers. Through the design of the game Teen Society, adolescents aged 11-24 years provided education about healthy association through mobile games.